Redefining in-game advertising: A systematic literature review and an updated definition - De-la-Vara-López, Javier (2024)
A precise definition of concepts is a fundamental pillar for constructing valid and reliable knowledge. Consistency in terminology is essential in order to use a common conceptual framework, avoid ambiguities, and facilitate comparability of studies. Following PRISMA guidelines, we ran a systematic literature review searching in Scopus and Web of science databases to identify and analyze the definitions of in-game advertising (IGA). Also, we ran a series of interviews with professionals from the advertising and video game industries in order to understand the professional view of the term. Confusion has been found in the use of IGA and related but different concepts, both in the literature and professional practice. Therefore, we presented a decision tree to facilitate coherent naming in the advertainment area of research and summarized all the research in a redefinition of IGA that synthesizes and updates the previous ones: is the integration of persuasive content, created for a real advertiser, that is part of the playable elements of a video game which has not been developed by the advertiser. This is the first study that uses a systematic approach to define IGA. The decision tree helps scholars and practitioners to clearly classify critical terms related to IGA (i.e., advertainment, advergaming, advergame, product placement, IGA, AGA). The updated definition and the decision three will help scholars to develop a more coherent literature on IGA and related concepts.